Konsep Pengelolaan Kontrak Bilateral yang Proporsional yang Menyeimbangkan Kepentingan Nasional dan Perlindungan untuk Investor Asing di Bidang Pertambangan - Ricky Bima Sanjaya; Bonaventura Ivan Mollet; Nofandi Irianto (Faculty of Law Hang Tuah University, 2020)
Investment policy is the main thing that must prioritize the national interest, not only in the field of new jobs but also must support the domestic eco-sector. In this case the state has an obligation to defend national interests. Specifically in terms of investment by managing contracts or bilateral investment treaty agreements (BIT) based on the Proportionality Principle. This principle is intended to provide justice and certainty for the parties. Bilateral Investment Treaties (BIT) agreements are considered important for the parties, which are related to the agreement. In the Bilateral Investment Treaties Agreement (BIT) are the most preferred clauses of the Nation, the National Treatment and Fair and Equitable Treatment, and the theory of state / government intervention that is considered to be able to balance national interests and protect investors in the mining sector.